2016
DOI: 10.1515/ace-2015-0116
|View full text |Cite
|
Sign up to set email alerts
|

Major Constructional Dispute Causes in Turkey

Abstract: The possibility of construction disputes can be reduced, but they cannot be avoided due to the uncertain and risky nature of the building industry. Conflicts between construction parties often have very unfavourable effects, such as cost increases, poor construction quality and time extension in the schedule. Lots of studies have been carried out in order to try and avoid these disagreements. However, there are no common resolution tools or techniques due to the improving conditions and scope of contracted wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Poor contract documentation was considered by various scholars as major causal factors incurring construction conflicts [69], [70]. With the aim of increasing the ease of contract reading, this study further revealed the underlying causes of readability problems in construction contracts.…”
Section: Implications For Contract Draftersmentioning
confidence: 72%
“…Poor contract documentation was considered by various scholars as major causal factors incurring construction conflicts [69], [70]. With the aim of increasing the ease of contract reading, this study further revealed the underlying causes of readability problems in construction contracts.…”
Section: Implications For Contract Draftersmentioning
confidence: 72%
“…Since then numerous researchers have examined the factors contributing to construction disputes in various countries including the USA (Mitropoulos and Howell, 2001), China (Chan and Suen, 2005), Australia (Love et al , 2010b), Thailand (Ayudhya, 2011), Ireland (Treacy et al ., 2016), New Zealand (Jelodar et al , 2015), Middle East (Awwad et al , 2016), Saudi Arabia (Mahamid, 2016; Assaf et al , 2019), Turkey (Yildizel et al , 2016), United Kingdom (Barman and Charoenngam, 2017) and Sri Lanka (Illankoon et al , 2019). Of these, Mitropoulos and Howell (2001) proposed a model for the determination of basic factors that drive the development of disputes by comparatively analyzing 24 construction disputes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of qualitative interviews helped to develop three categories for common sources of disputes as “project uncertainty, contract and process, people and behaviour issues.” The questionnaire survey by Awwad et al (2016) concluded that common dispute causes, as perceived by different stakeholders in the Middle East construction industry, were contractual causes including “opportunistic behaviour of contract parties, incomplete and contradictory contract documents, the ill-defined scope of work, and unfair risk apportionment.” A similar questionnaire survey conducted by Mahamid (2016) in Saudi Arabia also concluded that the top five factors causing disputes were “delay in progress payment by the owner, unrealistic contract duration, change orders, poor quality of completed works, and labour inefficiencies.” Another questionnaire survey among key stakeholders in large construction projects in Saudi Arabia was employed to rank the dispute factors and assess their relative significance (Assaf et al , 2019). According to the survey results, the most significant contributors to construction disputes were found to be “change or variation orders due to new requirements from the client, variations in quantities due to new requirements from the client, delay caused by contractor, design errors or omissions, and inconsistencies in the drawings and specifications.” Yildizel et al (2016) also applied the questionnaire method for the discussion of the current major constructional dispute reasons in Turkey. Questionnaire results demonstrated that the major factors causing disputes were “poor quality of performed works, delays in progress payments, inefficient site management, poorly written contracts, and design mistakes.” By investigating 48 legal cases in the United Kingdom, Barman and Charoenngam (2017) believed that core reasons for construction disputes can be grouped into five categories, which were “delay, defects, payment, termination, negligence, and performance.” A recent questionnaire survey conducted among professionals representing various stakeholders in Sri Lanka by Illankoon et al (2019) identified “failure to administer the contract, error omissions in contract documents, incomplete design information or employer requirement, failure to understand and/or comply with its contractual obligations, and poorly managed construction process” as the main factors leading to construction disputes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The growing demand and rapid growth of green buildings concept globally caused the construction key participants (architects, engineers, quantity surveyors, and environmentalists) to rethink the way buildings are constructed and the need to reduce the cost escalations and construction time frames [4]. Unfortunately, green buildings experience less successful project delivery [24] and despite the fact that the green building concept has many environments, social and economic advantages, there are still many issues clouding this new approach that slow down the growth of green buildings in Malaysia. According to previous research, it appears that green office building projects throughout the world face similar challenges, which are exacerbated by quality issues, schedule and cost overruns.…”
mentioning
confidence: 99%